High-stability transparent amorphous oxide TFT with a silicon-doped back-channel layer - Lee, Hyoung-Rae; Park, Jea-Gun (Journal of the Korean Physical Society, 2014)
We significantly reduced various electrical instabilities of amorphous indium gallium zinc oxide thin-film transistors (TFTs) by using the co-deposition of silicon on an a-IGZO back channel. This process showed improved stability of the threshold voltage ( V th ) under high temperature and humidity and negative gate-bias illumination stress (NBIS) without any reduction of IDS. The enhanced stability was achieved with silicon, which has higher metal-oxide bonding strengths than gallium does. Additionally, SiO X distributed on the a-IGZO surface reduced the adsorption and the desorption of H 2 O and O 2 . This process is applicable to the TFT manufacturing process with a variable sputtering target.